Kajian suhu ekstraksi panas dan konsentrasi bunga telang kering terhadap karakteristik fisikokimia dan organoleptik pudding - Tri Rahayuningsih; Marina Revitriani; Endang Noerhartati (AGROINTEK, 2022)
Pudding is well known as nutritious food and popular for all ages of consumers. One of determinant factors of consumer acceptance is food color, particularly in using natural colorants. Colored pudding was more attractive than colorless, especially by using natural dyes. Blue is one of the colors that attracting consumers. It can be extracted from dried butterfly pea flower (telang in Indonesian). The hot method extraction was the simplest natural dye extraction for household-scale industries. This study was aimed to determine the affected of the hot extraction temperature and the concentration of dried telang flower on the quality of pudding. The observed parameters were total anthocyanin content and color properties in terms of L*a*b. Sensory testing was used to evaluate color, taste, aroma, and texture preferences. The result showed that the interaction of the the treatments had a significant impact on the anthocyanin content, b* value, and panelists’ preference for color. The dried telang concentration affected brightness value (L*) and a* value. The concentration of telang flowers increased, resulting in a reduction in L* value. Also, a* value was affected by heat extraction temperature. Friedman’s test result showed that the treatments only had a significant effect on the panelists' preference for color. The panelists have very liked the color of pudding with heat extraction temperature 800C and concentration of dried telang flower 0.10%. The color was greenish-blue. This study recommend that dried telang flower can potentially as a pudding natural color.